2015
DOI: 10.1364/boe.6.000747
|View full text |Cite
|
Sign up to set email alerts
|

Efficient construction of robust artificial neural networks for accurate determination of superficial sample optical properties

Abstract: Abstract:In general, diffuse reflectance spectroscopy (DRS) systems work with photon diffusion models to determine the absorption coefficient μ a and reduced scattering coefficient μ s ' of turbid samples. However, in some DRS measurement scenarios, such as using short source-detector separations to investigate superficial tissues with comparable μ a and μ s ', photon diffusion models might be invalid or might not have analytical solutions. In this study, a systematic workflow of constructing a rapid, accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Our DRS system, which has been described in detail previously, consists of a supercontinuum source (NKT photonics, Denmark), an 1x4 optical switch (Piezosystem Jena, Germany) and a spectrometer equipped with a back-thinned CCD (QE65000, Ocean Optics, FL) capable of collecting light in the wavelength range from 500 to 1000 nm [13]. Two custom made optical fiber probes were employed in this study and the side view of the probes are shown in Fig.…”
Section: Measurement Setupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our DRS system, which has been described in detail previously, consists of a supercontinuum source (NKT photonics, Denmark), an 1x4 optical switch (Piezosystem Jena, Germany) and a spectrometer equipped with a back-thinned CCD (QE65000, Ocean Optics, FL) capable of collecting light in the wavelength range from 500 to 1000 nm [13]. Two custom made optical fiber probes were employed in this study and the side view of the probes are shown in Fig.…”
Section: Measurement Setupsmentioning
confidence: 99%
“…Cappon et al utilized an optical fiber probe to collect reflectance at SDSs of 0.23, 0.59, and 1.67 mm for estimating the superficial samples having optical properties comparable to those of brain tissues; they calculated the average probing depth of the probe was roughly less than 0.5 mm [12]. More recently, we employed a Monte Carlo simulation trained Artificial Neural Network (ANN) to recover skin optical properties from diffuse reflectance measured at SDSs of 1 and 2 mm [13].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve real time sample optical property recovery, we constructed an artificial neural network (ANN), which is trained by a database composed of numerous Monte Carlo simulation results, to efficiently determine the sample optical properties from the measured reflectance. The essential steps for constructing ANN models for this purpose were elaborated in our previous paper [13]. We employed the Matlab (Mathworks, MA) training function "trainbr" based on Bayesian regularization to update the weight and bias values according to LevenbergMarquardt optimization.…”
Section: Gpu-based Monte Carlo Model and Artificial Neural Networkmentioning
confidence: 99%
“…We constructed ANNs for this purpose. The essential steps of the construction and validation of these ANNs are very similar to those listed in our previous study [13] and are described in detail as follows.…”
Section: Ann Construction and Validationmentioning
confidence: 99%
See 1 more Smart Citation